Cellular Mechanism and Arrhythmogenic Potential of T-Wave Alternans in the Brugada Syndrome - FISH, JEFFREY M. (2007)
INTRODUCTION: T-wave alternans (TWA) is characterized by beat to beat alteration in the amplitude, polarity and/or morphology of the electrocardiographic T wave. TWA has been reported in patients with the Brugada syndrome (BS) and is thought to be associated with an increased risk for development of VT/VF. The cellular mechanisms involved are not well-defined and are the subject of this investigation. METHODS: In an experimental model of BS composed of an arterially perfused canine right ventricular wedge preparation pretreated with verapamil (1–7 μM), an agent with sodium and calcium channel blocking activity, we simultaneously recorded transmembrane action potentials from two epicardial and one endocardial site, together with a pseudo-ECG. At select frequencies, verapamil induced alternans of both the T-wave amplitude and QT interval. The alternans resulted from either loss of the epicardial action potential dome on alternate beats or concealed phase 2 reentry within the epicardium on alternate beats. Loss of the epicardial action potential dome significantly increased transmural dispersion of repolarization (TDR) when compared with control (18.0 ± 7.8 ms vs. 82.1 ± 16.8 ms, P < 0.001, n = 8). During alternans, TDR was greater in beats displaying a more negative T wave (55.1 ± 45.2 ms vs. 89.8 ± 39.3 ms, P < 0.001, n = 22 data points from 8 preparations). CONCLUSIONS: Our data indicate that TWA in an experimental model of the Brugada syndrome is due to alternating loss of the epicardial AP dome and/or concealed phase 2 reentry, both serving to increase TDR and create the substrate for the development VT/VF.